Satisfaction and Loyalty in Cultural Heritage Tourism: Analysis of Destination Brand Experience Dimensions at Taman Mini Indonesia Indah - Adam Faisal Faliti; Andreo Wahyudi Atmoko (CV. Syntax Corporation Indonesia, 2025)
This study investigates a counterintuitive phenomenon in the context of cultural heritage tourism, where the Destination Brand Experience (DBE) dimensions that drive visitor satisfaction differ from those that influence tourist loyalty. The research is conducted at Taman Mini Indonesia Indah (TMII), analyzing data from 200 respondents who visited the destination after the revitalization process during the 2022–2025 period. Utilizing a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the analysis reveals that sensory, affective, and behavioral experiences significantly influence visitor satisfaction levels (β = 0.201; 0.301; 0.384; p < 0.05). However, only intellectual experience is shown to have a direct impact on revisit intention (β = 0.177; p < 0.01). This finding challenges the fundamental assumption in tourism literature that satisfaction automatically leads to loyalty. The study contributes to the advancement of destination branding theory by demonstrating that satisfaction and loyalty do not always originate from the same experiences, but instead follow different psychological pathways as explained in Experience Economy Theory. The implication is that cultural heritage destination managers must design strategies that not only aim for short-term satisfaction through entertainment but also foster long-term visitor loyalty by providing transformative educational experiences.